DEVELOPMENT OF PROJECT-BASED LEARNING MODEL INSTRUCTIONAL DESIGN TO IMPROVE JUNIOR HIGH SCHOOL STUDENTS' LITERACY - Rohmah, Nurul Anzili; Machsunah, Yayuk Chayatun (Journal on Research and Review of Educational Innovation, 2023)
This article discusses how the use of the Project Based Learning (PjBL) model can improve students' literacy skills. PjBL is one of the innovative learning models, where learning is more student-centered, using projects as learning media. The purpose of this research is to analyze the effectiveness of the PjBL learning model in improving students' literacy skills. Literacy includes the knowledge and skills needed by learners to access, understand, analyze, and evaluate information, create meaning express thoughts and emotions, and generate ideas and opinions. One aspect of literacy skills is reading literacy. Therefore, efforts are needed to improve students' reading literacy skills, one of which is by using the PjBL learning model. In this PjBL model, students are invited to discuss with groups about the theme of the Diversity of Indonesian Communities in Unity in Diversity with problems encountered in everyday life.